2019
DOI: 10.1111/cup.13516
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ZNF750 in ocular and cutaneous sebaceous carcinoma

Abstract: Background: Sebaceous carcinoma (SeC) is an uncommon malignancy arising from sebaceous glands of the conjunctiva and skin. Recurrent mutations in the ZNF750 were recently identified in ocular SeC. We assessed whether ZNF750 loss is a specific feature of ocular SeC or a general feature of sebaceous tumors.Methods: Immunostaining for ZNF750 expression was performed in 54 benign and malignant sebocytic proliferations. Staining for ZNF750 was scored on a three-tier scale: positive (>75%), partially positive (5%-74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Loss of expression of ZNF750 was detected exclusively in a subset of SC compared with benign sebaceous proliferations. 20 However, its specificity is uncertain because it has been reported that ZNF750 acts as a tumor suppressor in a variety of SCCs. 21 The potential difficulty in the recognition of basaloid SC arises not only because of the morphologic overlap with other cutaneous basaloid neoplasms, but also because of the nonspecific immunohistochemical profile of many of the entities in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of expression of ZNF750 was detected exclusively in a subset of SC compared with benign sebaceous proliferations. 20 However, its specificity is uncertain because it has been reported that ZNF750 acts as a tumor suppressor in a variety of SCCs. 21 The potential difficulty in the recognition of basaloid SC arises not only because of the morphologic overlap with other cutaneous basaloid neoplasms, but also because of the nonspecific immunohistochemical profile of many of the entities in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of expression of ZNF750 was detected exclusively in a subset of SC compared with benign sebaceous proliferations. 20 However, its specificity is uncertain because it has been reported that ZNF750 acts as a tumor suppressor in a variety of SCCs. 21…”
Section: Discussionmentioning
confidence: 99%
“…The different expression pattern of beta‐catenin, LEF1, and Shh in ocular and extraocular SC may result from intrinsic differences of these two types of SC. For example, ZNF750, which controls epithelial homeostasis by regulating epidermal differentiation, was also differentially expressed in ocular and extraocular SC 22 …”
Section: Discussionmentioning
confidence: 99%
“…For example, ZNF750, which controls epithelial homeostasis by regulating epidermal differentiation, was also differentially expressed in ocular and extraocular SC. 22 The aberrant hedgehog signaling and LEF1 loss-of-function in carcinogenesis of extraocular SC may not be exclusively independent. In fact, there is evidence of interaction between Wnt/beta-catenin and hedgehog signaling.…”
Section: Impaired Wnt/beta-catenin and Ptch Signaling In Extracutaneo...mentioning
confidence: 99%
“…Two other commonly mutated genes in SGC are ZNF750 [14], particularly in the aforementioned pauci-mutational group, and PCDH15 [13], significantly associated with nodal and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%